Assessing the effectiveness of conventional notice board in universities’ information delivery / Roslilee Ab.Halim...[et al.] - Ab.Halim, Roslilee; Abd Jabar, Faizan; Mohamad, Siti Aishah; Azer, Ilyani; Ab.Halim, Norliwa (Universiti Teknologi MARA Cawangan Pahang, 2011)
The conventional wooden notice board is widely used in most universities all over the world as a tool to make an-nouncement or deliver latest information to students. However, as the information technology (IT) is advancing, it changes the way we live, communicate, learn and do business as well. As the young generation embraced technol-ogy and became attached to it, universities or higher education institutions had to keep up with the transformation in ensuring daily activities run smoothly. Therefore, the aim of this paper is to investigate the effectiveness of information delivery in higher education institutions. Do these young IT savvy students go and read announcement or information from the notice board or do they opt to read them from the virtual notice board? Do the announcement or information updates on the notice board reach the students or do we have to develop a friendly virtual notice board that could be accessed from anywhere? The population of this study consists of students from Univer-siti Teknologi MARA Cawangan Pahang. Six diploma programmes were randomly chosen and a total of 356 ques-tionnaires were distributed. The selection of sample was based on stratified random sampling technique. The SPSS Version 18.0 was used to conduct data analysis. Data was analyzed for descriptive statistics such as mean, frequency and percentage.